Pemikiran Fikih Muhammad ibn Isma’il Al-Bukhary - Muh. Fathoni Hasyim (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2008)
The discourse of Islamic legal thought has unfolded and been established since the emergence of so-called the ‎eponyms of Islamic school of law. However, Mujtahids which have expertise in hadith or Prophetic Tradition are ‎rarely studied. Al-Bukhary who is an expert of Prophetic Tradition is one of those jurists. His name is unquestioned ‎whenever people talk about hadith. His expertise in hadith has led him to deal with many legal issues and finally ‎gave him expertise in Islamic jurisprudence. This second expertise of al-Bukhary is not well known to many ‎Muslims although his expertise in Islamic jurisprudence had reached the highest level; the level of mujtahid mutlaq ‎‎(absolute legal interpreter) or mujtahid mustaqill (ilk;ndependent legal interpreter). It enables him to independently ‎deduce law since he is not bound to any school of law. Some of Al-Bukhary’s legal opinions are often contradictory ‎to the majority of Islamic jurists. Two examples of his opinions is cited in this article; major bath is not obligatory if ‎sexual intercourse is not concluded with inzal (ejaculation); and that thigh is not part of ‘aurah (privy part).‎